2019
DOI: 10.1002/acn3.50930
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and malignancy risk of different FUS mutations in genetic amyotrophic lateral sclerosis

Abstract: ObjectiveMutations in Fused in Sarcoma (FUS or TLS) are the fourth most prevalent in Western European familial amyotrophic lateral sclerosis (ALS) populations and have been associated with causing both early and very late disease onset. FUS aggregation, DNA repair deficiency, and genomic instability are contributors to the pathophysiology of FUS‐ALS, but their clinical significance per se and their influence on the clinical variability have yet to be sufficiently investigated. The aim of this study was to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 30 publications
7
39
0
Order By: Relevance
“…In this work we took advantage of pure populations of hiPSC-derived motoneurons to study the impact of a FUS mutation, linked to severe and juvenile ALS 15 , on the human motoneuron proteome. Interestingly, GO term enrichment analysis suggested that proteins involved in catabolic processes and oxidation-reduction are upregulated in FUS mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this work we took advantage of pure populations of hiPSC-derived motoneurons to study the impact of a FUS mutation, linked to severe and juvenile ALS 15 , on the human motoneuron proteome. Interestingly, GO term enrichment analysis suggested that proteins involved in catabolic processes and oxidation-reduction are upregulated in FUS mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical classification of ALS associated with FUS mutation has been designated as familial ALS type 6 (ALS6; Vance et al, 2009). Most patients with ALS6 appear to be predominantly lower motor neuron with young onset, aggressive course, high incidence of bulbar symptoms, and early respiratory involvement, although typical ALS phenotype and slower disease course have also been described in some patients (Naumann et al, 2020; Sproviero et al, 2012). FUS mutations have been reported to be responsible for 3%–4% of familial ALS and for less than 1% of sporadic ALS (Zou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They have been demonstrated to affect subcellular distribution or increase the propensity to form cytoplasmic FUS-positive granules [ 105 ], with effects going beyond an expected, albeit partial, loss of function. From a clinical point of view, these frameshift variants are frequently associated with a juvenile and rapidly progressive form of ALS [ 106 ]. A specific nonsense variant, c.868C > T (commonly referred to as p.Glu290 *), has been identified as the cause of essential tremor in a large family [ 107 ].…”
Section: Applying the Acmg Standards And Guidelines For The Interpmentioning
confidence: 99%